Analisis Pengaruh Pertumbuhan Ekonomi, Tingkat Pengangguran, dan Jumlah Penduduk Terhadap Kemiskinan di 5 Negara ASEAN - Ramadhani, Affni; Setyowati, Eni (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Poverty is a multifaceted economic issue that necessitates strategies to mitigate or diminish its prevalence within a nation. The objective of this study is to examine the impact of economic growth, unemployment rate, and population on poverty in five ASEAN countries. The data utilized to address this issue includes panel data, spanning from 2010 to 2020, and encompassing the data volume from five ASEAN countries. The study findings indicate that the Fixed Effect Model (FEM) method was selected as the employed model. Observing the data reveals that the economic growth variable has a negligible and inconsequential impact, however unemployment and population have a noteworthy and meaningful impact on poverty in 5 ASEAN countries.